Moral distress and spiritual/religious orientation: Moral agency, norms and resilience - Koonce, Myrna (Nursing ethics, 2023)
BackgroundNurses tasked with providing care which they perceive as increasing suffering often experience moral distress. Response to moral distress in nurse wellbeing has been widely studied. Less research exists that probes practicing nurses’ foundations of moral beliefs.AimsThe purpose of this phenomenological study was to gain understanding of nurse meaning-making of morally distressing situations, with particular attention to ethical norms, moral agency and resiliency, and nurse religious/spiritual orientation.DesignThis exploratory study employed semi-structured interviews using open-ended questions. Qualitative data analysis was assisted by MAXQDA software.Participants and research contextNine pulmonary care nurses during COVID-19 in a tertiary care teaching hospital in the northeastern United States.Ethical considerationsThe study was approved by the IRB. Participants were consented before the study and confidentiality was preserved.Findings/resultsThe study revealed three main themes of meaning-making, rooted in the identity of the “good nurse”: Being true to one’s own values, pursuing ideal patient care (“doing good”), and conforming to/challenging values of the system and culture. Tensions were found between (a) nurse’s own values (b) duty to institutional norms and duty to nurse’s personal code of ethics, and (c) perceptions of institutional support in response to nurse moral distress. Religion was described as a remote source of nurse moral values, among other sources. Spiritual practices were not experienced as sufficient in coping with moral distress at the bedside.ConclusionsThe study suggests nurses need more opportunities to engage in reflection on their practice and values. The findings also indicate need for accessible institutional supports for nurses experiencing moral distress and strategic use of chaplains in helping with moral distress. Further research is needed on the interplay of nurse spirituality, moral agency, and reflective practice in the face of morally challenging situations.